Danger Signals Activating the Immune Response after Trauma. (19th June 2012) - Hirsiger, Stefanie; Simmen, Hans-Peter; Werner, Clément M. L.; Wanner, Guido A.; Rittirsch, Daniel
Abstract : Sterile injury can cause a systemic inflammatory response syndrome (SIRS) that resembles the host response during sepsis. The inflammatory response following trauma comprises various systems of the human body which are cross-linked with each other within a highly complex network of inflammation. Endogenous danger signals (danger-associated molecular patterns; DAMPs; alarmins) as well as exogenous pathogen-associated molecular patterns (PAMPs) play a crucial role in the initiation of the immune response. With popularization of the "danger theory, " numerous DAMPs and PAMPs and their corresponding pathogen-recognition receptors have been identified. In this paper, we highlight the role of the DAMPs high-mobility group box protein 1 (HMGB1), interleukin-1 α (IL-1 α ), and interleukin-33 (IL-33) as unique dual-function mediators as well as mitochondrial danger signals released upon cellular trauma and necrosis.